2018
DOI: 10.30658/jicrcr.1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Health Belief Model and Preventive Measures: A Study of the Ministry of Health Campaign on Coronavirus in Saudi Arabia

Abstract: As of August 2017, approximately 684 people have died in the Kingdom of Saudi Arabia since the coronavirus Middle East respiratory syndrome (MERS-CoV) outbreak in 2012. Saudi Arabia became the leading country for the number of illnesses and deaths related to MERS-CoV, making this a health megacrisis. Early Ministry of Health (MOH) communication efforts proved ineffective and created anger, confusion, and mistrust. Changes in command, implementation of new guidelines and policies, and a health preventive campai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
3
31
1
1
Order By: Relevance
“…We extended work on the relationship between dark personality and health, examining preventive and hoarding behaviors during the COVID-19 pandemic ( Sternisko et al, 2020 ; Zajenkowski et al, 2020 ). Our study pointed to the utility of the health belief model ( Alsulaiman & Rentner, 2018 ; Rosenstock, 1974 ; Rosenstock et al, 1988 ) in predicting such behaviors, with beliefs serving as mechanisms linking personality to engaging in adaptive (i.e., preventive) and maladaptive (e.g., hoarding) preventative measures. We advanced the scope of the model by illustrating the relevance of dark personality traits in predicting both adaptive and maladaptive behaviors in response to the pandemic by person-focused (i.e., the Dark Triad traits) and group-focused (i.e., collective narcissism) personality traits.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We extended work on the relationship between dark personality and health, examining preventive and hoarding behaviors during the COVID-19 pandemic ( Sternisko et al, 2020 ; Zajenkowski et al, 2020 ). Our study pointed to the utility of the health belief model ( Alsulaiman & Rentner, 2018 ; Rosenstock, 1974 ; Rosenstock et al, 1988 ) in predicting such behaviors, with beliefs serving as mechanisms linking personality to engaging in adaptive (i.e., preventive) and maladaptive (e.g., hoarding) preventative measures. We advanced the scope of the model by illustrating the relevance of dark personality traits in predicting both adaptive and maladaptive behaviors in response to the pandemic by person-focused (i.e., the Dark Triad traits) and group-focused (i.e., collective narcissism) personality traits.…”
Section: Discussionmentioning
confidence: 76%
“…One pertinent theoretical model, the health belief model, proposes five classes of such beliefs: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and additionally cues to action ( Rosenstock, 1974 ; Rosenstock, Strecher, & Becker, 1988 ). This model has been applied to the MERS-Cov coronavirus infection ( Alsulaiman & Rentner, 2018 ) to understand compliance with measures recommended by the Saudi Arabian government, a situation resembling the current pandemic. We regarded individual differences in these beliefs as putative mediators between personality traits and health-related behaviors in relation to COVID-19.…”
mentioning
confidence: 99%
“…There is theoretical and empirical evidence demonstrating the value of constraints in predicting the adoption of recommended behaviors in pandemics. For example, during the COVID-19 outbreak, people who had higher outcome expectations about engaging in avoidant behaviors were more likely to follow the recommended guidelines [ 61 ]. Assessments about self-efficacy also positively impacted intentions to self-isolate during COVID-19, and influenced Americans’ avoidance of domestic travel during the Ebola outbreak [ 62 , 63 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of health beliefs on disease-preventive behaviors have been widely validated in numerous empirical studies [ 22 , 24 , 25 , 26 ]. For instance, Yoshitake, Omori, Sugawara, Akishinonomiya, Shimada, and Iannello [ 22 ] found that perceived susceptibility to tuberculosis positively predicted the frequency of engaging in preventive behaviors such as wearing surgical masks in public.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yoshitake, Omori, Sugawara, Akishinonomiya, Shimada, and Iannello [ 22 ] found that perceived susceptibility to tuberculosis positively predicted the frequency of engaging in preventive behaviors such as wearing surgical masks in public. Similarly, Alsulaiman and Rentner [ 26 ] found that study participants in Saudi Arabia who had higher levels of perceived susceptibility and severity regarding the coronavirus Middle East respiratory syndrome, and higher levels of perceived benefits and lower levels of perceived barriers regarding preventive behaviors, were more likely to implement disease-preventive behaviors recommended by the government. In terms of the COVID-19 pandemic, it has also been found that perceived susceptibility, perceived severity, and perceived benefits positively predicted, and perceived barriers negatively predicted, the frequency of engaging in preventive behaviors such as staying at home unless it is for essential activities [ 24 ].…”
Section: Introductionmentioning
confidence: 99%